Personality Development the Common Need of Modern Era: Exploring the Impact of Personality Development on Modern Individuals (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The world is one among influencing a part of our energy which is employed within the preservation of our bodies. Outside that, every particle of our energy is day and night in influencing others. Our bodies, our virtues, our intellect, and our spirituality, of these, are always influencing others then, conversely, we are being influenced by them. The science of yoga claims that is covered the laws and methods which certainly develop the personality of each person by giving proper attention and guidance. It could enable scholars to grow and strengthen their personality. The purpose of education is to equip students with the potential to fulfill challenges in their lives. When someone is fully equipped with education, he could understand his capabilities, strengths, and weakness so there would be less scope for all such mishaps that might disturb his life. So, education leads students towards the role of personality development. As far as students are concerned, effective personality development programs can aid them in managing the challenges of the skin world more effectively and efficiently. This can also help them in understanding the small print involved within the corporate world. Personality Development is most vital that each one other sort of development of economic, educational, and rural, etc. because of these other forms of development are undertaken just for the advantage of man. Most people don’t purposely develop their personality as they are not tuned in to it our appearance, speech and action become apparent to us only through others as we don’t see ourselves or our behavior. This Research work is undertaken with the objective of making analysis of factors that could impact personality of any person. This article also provides various measures which could help anyone to develop their personality, to make them perfect for today’s growing need.